Anthropology of Salvation in Russian Medieval thought: «Nestyazhateli» and «Iosiflyanie» - Borisovich Lebedev, Alexey; Vladimirovich Tokranov, Alexander; Vladislavovna Kuzmina, Elena (International Journal of Criminology and Sociology, 2022)
This article analyzes the anthropocentric aspects of Russian Orthodox thought. It is noted that the Russian traditional self-consciousness inherited the main religious and moral norms and values of Byzantium, such as contemplation, Hesychasm, careful preservation of dogmatic and ceremonial aspects of faith. The authors of the article conclude that the central problem in Russian Orthodox thought is the problem of human justification, the problem of understanding human essence. Starting with the understanding of the problem of theodicy, Russian Orthodox thought gradually turned into its visibly formal opposite and became essentially a philosophy that proves the high creative purpose of man - a philosophy that justifies man. Thus, the humanistic, anthropocentric direction of the development of Russian religious philosophy is emphasized. Also, turning to the analysis of the dispute between «Iosiflyane» and «Nestyazhateli», the authors of the article identify two opposite conceptual approaches to the philosophical interpretation of the essence of man: «contemplative man» and «active man».The authors conclude that Russian state policy has been mostly «Iosiflyanian», and the philosophy became a haven for «Nestyazhatel».